Is Social Integration Necessary for Corporate Branding?: A study of corporate branding strategies at Novo Nordisk - Jacob Holm Hansen (Copenhagen Business School (CBS), 2012)
The inspiration for this project came from a practical and a theoretical interest in how strategies are anchored in organisations. In 2005 a colleague and I published a book about strategic leadership communication (Bordum and Holm Hansen 2005). It was an inquiry into how the power of strategic statements, such as vision, mission and values, are rooted in the underlying forces of communication and actions among the stakeholders of organisations. It demonstrated that the drivers of successful leadership are based on persuasive communication and action. This project takes this line of thought further through a conceptual and empirical inquiry. It is motivated by an interest in basic knowledge about corporate branding as an integrative phenomenon. Corporate branding is often understood as a strategic activity that creates attention and value for a company. The strategic and managerial approaches are generally dominant in theory and practice, where they suggest various prescriptions for success with a corporate branding project. Such approaches often build on assumptions about control where certain consecutive steps automatically lead to a powerful brand. While there are many possible approaches to corporate branding, it seems that the question of integration is a salient issue that characterises the phenomenon in different ways. For instance, corporate branding is said to integrate various academic disciplines, provide an integrated profile of a company, integrate internal and external stakeholders, etc. The particular focus here is encouraged by questions and reflections about how corporate branding as an integrative activity can be analysed and understood through a pragmatic theory of communication.
hdl:10398/8456
Keywords: 650